Masterclass Proficiency: Student's Book - Gude K.; Gude Kathy; Duckworth Michael (Oxford Oxford University Press, 2002)
Proficiency Masterclass has a well-established reputation as a successful training programme for the CPE exam. Now revised and extended, this new edition of Proficiency Masterclass includes all the information and guidance students need to prepare confidently for the revised CPE exam.
Keywords: 811.111